Influence of multi‐wavelength laser irradiation of enamel and dentin surfaces at 0.355, 2.94, and 9.4 μm on surface morphology, permeability, and acid resistance. Issue 10 (12th July 2017) - Chang, Nai‐Yuan N.; Jew, Jamison M.; Simon, Jacob C.; Chen, Kenneth H.; Lee, Robert C.; Fried, William A.; Cho, Jinny; Darling, Cynthia L.; Fried, Daniel
Abstract : Objective: Ultraviolet (UV) and infrared (IR) lasers can be used to specifically target protein, water, and mineral, respectively, in dental hard tissues to produce varying changes in surface morphology, permeability, reflectivity, and acid resistance. The purpose of this study was to explore the influence of laser irradiation and topical fluoride application on the surface morphology, permeability, reflectivity, and acid resistance of enamel and dentin to shed light on the mechanism of interaction and develop more effective treatments. Methods: Twelve bovine enamel surfaces and twelve bovine dentin surfaces were irradiated with various combinations of lasers operating at 0.355 (Freq.‐tripled Nd:YAG (UV) laser), 2.94 (Er:YAG laser), and 9.4 μm (CO2 laser), and surfaces were exposed to an acidulated phosphate fluoride gel and an acid challenge. Changes in the surface morphology, acid resistance, and permeability were measured using digital microscopy, polarized light microscopy, near‐IR reflectance, fluorescence, polarization sensitive‐optical coherence tomography (PS‐OCT), and surface dehydration rate measurements. Results: Different laser treatments dramatically influenced the surface morphology and permeability of both enamel and dentin. CO2 laser irradiation melted tooth surfaces. Er:YAG and UV lasers, while not melting tooth surfaces, showed markedly different surface roughness. Er:YAG irradiation led to significantly rougher enamel and dentin surfaces and led to higher permeability. There were significant differences in acid resistance among the various treatment groups. Conclusion: Surface dehydration measurements showed significant changes in permeability after laser treatments, application of fluoride and after exposure to demineralization. CO2 laser irradiation was most effective in inhibiting demineralization on enamel while topical fluoride was most effective for dentin surfaces. Lasers Surg. Med. 49:913–927, 2017. © 2017 Wiley Periodicals, Inc.